A possibilidade de uma literatura engajada a partir de Jean-Paul Sartre - Mello, Daniel Pereira de (2017)
The main objective of this research is to study Jean-Paul Sartre’s notion of literary engagement, specially the one presented in his book What Is Literature? Considering that there is no definitive formulation of the concept throughout his philosophical works and, moreover, that such a concept cannot be described apart from his phenomenology, the research starts with the study of the imaginary in Sartre’s thought. This approach turned out to be critical, since, to him, the artistic production (and consequently the literature itself) is a product resulting from the creation of an unreal. Thus, with the study of the imaginary we pursue the theoretical elements that allow us to achieve a better understanding of engagement in the prose form. Lastly, intending to comprehend the literary production in a broader sense, we analyze questions pertaining to the problem of liberty and how literature is defined as an objected constructed by both, the writer and the reader.